Tuna Wicara Model Penanganan Anak Berkebutuhan Khusus Tuna Wicara pada Sekolah Jalan Ceurih Kecamatan Ule Kareng, Kota Banda Aceh - Zakia Husna; Silvia Rizki; Fitriani Fitriani; Ulfa Amalia (Institut Nalanda, 2025)
This research aims to describe strategies for handling children with speech impairments at PAUD Aceh Flexi School. Speech-impaired children are part of Children with Special Needs (ABK) who experience obstacles in verbal communication, so they require a special learning approach and support. This research uses a qualitative approach with a case study method. Data was collected through observation, interviews and documentation, with the research subjects consisting of a teacher and one speech-impaired child. The research results show that treatment is carried out through three main stages: initial identification, implementation of adaptive learning strategies, and parental involvement. Learning strategies include the use of visual media, sign language, and a total communication approach that helps children express themselves. Teachers also form collaborative communications with parents to strengthen stimulation at home. However, there are obstacles such as limited communication aids, lack of teacher training, and lack of parental awareness. This research emphasizes the importance of a collaborative, communicative and empathetic approach in inclusive education to optimize the potential of children with speech impairments from an early age.